High-Sensitivity Gas Pressure Sensor Based on Fabry–Pérot Interferometer With a Side-Opened Channel in Hollow-Core Photonic Bandgap Fiber - Jian Tang; Guolu Yin; Changrui Liao; Shen Liu; Zhengyong Li; Xiaoyong Zhong; Qiao Wang; Jing Zhao; Kaiming Yang; Yiping Wang (IEEE Photonics Journal)
We demonstrate a high-sensitivity gas pressure sensor by use of an in-fiber Fabry–Pérot interferometer (FPI) based on hollow-core photonic bandgap fiber (HC-PBF) with a side-opened channel. The FPI was constructed by splicing a thin piece of HC-PBF between two stander single-mode fibers. Then, a side-opened channel was drilled through the hollow core of the HC-PBF by use of a femtosecond laser. Such an FPI with a side-opened channel greatly enhanced the gas pressure sensitivity up to 4.24 nm/MPa, which is two orders of magnitude higher than that of FPI with an enclosed cavity. In addition, the effects of cavity length on the gas pressure sensing performance were also studied. A shorter cavity gives rise to broader measurement range while offering larger detection limit, and vice versa. The structure size is tens of micrometers, which makes it possible to develop an ultracompact high-sensitivity gas pressure sensor.